Field notes contributed by Jim Sinclair, fall 1984 - Sinclair, Jimet al (1984)
Field notes were contributed by Jim Sinclair, fall 1984. A Northern Goshawk sighting is noted. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1984. Epson - sheet feed